Anisotropy of Ternary and (Zr,Ga) Addition Magnetic Powders (Journal of Atomic and Molecular Sciences, 2021)
Both non-homogenization treatment Zr, Ga addition and ternary Strip Castingalloy flakes can be used to prepare anisotropy HDDR NdFeB magnetic powders.This illustrates that anisotropy formation of magnetic powders neither depends onelement addition nor depends on homogenization heat treatment of SC flakes. Butthe HDDR process procedure also plays an important role in anisotropy inducement.Highly anisotropic magnetic powders are attributed to rapid disproportionation reactioncourse, slow desorption-recombination reaction course, and optimum recombinationhydrogen pressure during HDDR procedure process. This paper will provide animportant guidance for preparing highly anisotropy magnetic powders with low cost.